Hosts and Guests: Hospitality as an Emerging Paradigm in Mission - Brandner, Tobias (International review of mission, 2013)
In recent years, hospitality has turned into a central term in missiological discussions integrating several aspects of missiological reflection. The essay summarizes how the dialectic between host and guest builds a central thread throughout the biblical narrative and explores how the dual role of missionaries as hosts and guests opens new dimensions of missionary existence and self-understanding. On the one hand, the role of the missionary as guest emphasizes the missionary's vulnerability and voluntary submission to the cultural and contextual rules. It thus implies a humility that stands in contrast to any spirit of conquest. On the other hand, missionaries who understand their role as one of host show a readiness for disruption and openness to the sacramental quality of a guest that possibly allows an encounter with God. Hospitality thus re-enacts a basic movement of faith, the movement of receiving the alien word of God. In a final reflection, the essay considers a contradiction inherent in the concept of hospitality, as pointed out by the French philosopher Jacques Derrida, the contradiction between openness to those in need of hospitality and the host's dependence on power and control in order to host people.